The Implementation of Arbitral Award Annulment In Judicial Practice - Hetty Maria Pasaribu; Dhaniswara K. Harjono; Bernard Nainggolan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study attempts to identify the procedure for annulling an arbitral award through the courts and the legal framework governing it. The author uses Gustav Radbruch's legal theory the theory of justice, legal certainty, and legal consequences as an instrument to examine and explain the mechanism for annulling an arbitral award, the types of legal remedies available, and their legal consequences. Using this approach, the author can assess whether an annulment request for an award can be submitted based on the grounds stipulated in law, as well as identify the legal steps that can be taken and their legal impact. The method used is normative legal research, which compiles legal sources by referring to norms in statutory regulations, court decisions, and social customs. The legal sources analyzed include primary materials authoritative documents such as laws, official records, legal treatises, and judicial decisions and secondary materials, namely non-official publications such as textbooks, legal dictionaries, journals, and commentaries on court decisions. Based on the findings, the author concludes that the arbitration award is final and binding on the parties. However, an annulment can be requested if the three conditions stipulated in Article 70 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution are met. Because it is a special civil case, there is no appeal to the High Court; the term